2018
DOI: 10.3390/ma11071083
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silicon Particles Favor the Induction of Long-Lived Humoral Responses in Mice to a Peptide-Based Vaccine

Abstract: Vaccinology faces the challenge of developing improved immunization approaches that are able to induce long-term immunity with the desired Th profile according to the pathology. In this context, new vehicles for efficient antigen delivery that exert adjuvant effects play a critical role in addressing this goal. Herein, mesoporous silicon particles (PSiP) were assessed as carriers for a peptide-based vaccine targeting the receptor for advanced glycation end products (RAGE), which is a relevant receptor in Alzhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…111,117,118 Rosales-Mendoza et al prepared a peptidebased vaccine based on negatively charged pSi nanocarriers loaded with positively charged, advanced glycation end products (RAGE) peptide, for the treatment of immune diseases such as Alzheimer's. 114 In vivo results confirmed that the SC injected peptide loaded pSiNPs increased the prolonged efficacy of immunization by significantly longer humoral responses compared to free peptide injection (up to 52 days). 114 Molecular interactions of RAGE and pSi particles at the physiologic condition were responsible for the enhancement of the immunogenic activity of RAGE.…”
Section: Micro-and Nanoparticle-based Peptide Delivery Formulationsmentioning
confidence: 58%
See 4 more Smart Citations
“…111,117,118 Rosales-Mendoza et al prepared a peptidebased vaccine based on negatively charged pSi nanocarriers loaded with positively charged, advanced glycation end products (RAGE) peptide, for the treatment of immune diseases such as Alzheimer's. 114 In vivo results confirmed that the SC injected peptide loaded pSiNPs increased the prolonged efficacy of immunization by significantly longer humoral responses compared to free peptide injection (up to 52 days). 114 Molecular interactions of RAGE and pSi particles at the physiologic condition were responsible for the enhancement of the immunogenic activity of RAGE.…”
Section: Micro-and Nanoparticle-based Peptide Delivery Formulationsmentioning
confidence: 58%
“…In vivo results confirmed that the SC injected peptide loaded pSiNPs increased the prolonged efficacy of immunization by significantly longer humoral responses compared to free peptide injection (up to 52 days) . Molecular interactions of RAGE and pSi particles at the physiologic condition were responsible for the enhancement of the immunogenic activity of RAGE . In another study, Herzig et al designed thermally hydrocarbonized pSi (THCpSi) MPs with 38–53 μm size for the delivery of peptide Melanotan II .…”
Section: Micro- and Nanoparticle-based Peptide Delivery Formulationsmentioning
confidence: 80%
See 3 more Smart Citations